A Comparative Study of Two Types of Implantation Surgery Methods for Implantable Collamer Lenses. (20th November 2021) - Liu, Hao; Dong, Denghao; Chen, Chunlin; Ye, Jian
Abstract : Purpose . To investigate the effects of two different surgical methods of implantable collamer lens (ICL) implantation on the operation time, visual outcomes, corneal endothelial cell count, and intraocular pressure (IOP). Methods . This was a contralateral eye comparison study, a total of 192 eyes from 96 patients were included, and the two eyes from the same patient were randomly assigned to two groups (group 1 and group 2, with 96 eyes in each group). In group 1, after making the corneal incision, ophthalmic viscosurgical devices (OVDs) were first injected into the anterior chamber followed by ICL implantation. In group 2, the ICL was first implanted into the anterior chamber followed by OVDs injection. The operation time, uncorrected distance visual acuity, corrected distance visual acuity, spherical equivalent, corneal endothelial cell count, and IOP were recorded and analyzed. Results . The operative time in group 1 was significantly longer than that in group 2 (P  = 0.002 < 0.05). There were significant differences between IOP measured 2 hours following surgery of the two groups (P  = 0.026 < 0.05), Furthermore, the rate of IOP change 2 hours following the operation was significantly higher in group 1 than in group 2 (P  = 0.019 < 0.05). There were significant differences in the anterior chamber angle 2 hours after surgery compared with that before surgery in both groups (P  = 0.014 < 0.05 and P  = 0.029 < 0.05, respectively). No significant differences were observed in the other parameters measured (all P  > 0.05). Conclusion . The two ICL implantation methods had similar clinical outcomes and effects on the corneal endothelial cell count. Additionally, the implantation of an intraocular lens prior to injecting OVDs reduces the operation time and lowers the rate of IOP rise in the early postoperative period, making it safe and effective for ICL implantation.